Study of anterior structures formation in Xenopus laevis: insights on the role of novel gene XADTK2 in Xenopus embryogenesis - Burlacu, Marta Isabel Martins Vitorino (2011)
Tese de dout., Biologia, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2009